Memory Power: Memory-boosting puzzles and facts to improve your memory - Michael Powell (Parragon, 2014)
Do you wish you had a better memory? Are you always losing things? Do you want to improve your general knowledge? This practical book is packed with memory-boosting ideas and challenges. With scores of fun and testing exercises, puzzles and quizzes, Memory Power will develop your concentration, improve your recall and sharpen your memory. Each section provides a fascinating overview of a specific memory topic or skill followed by compelling activities to give your brain a targeted workout. Remember names and faces Improve your study skills Become a quiz whiz Never forget your PIN or passwords again The brain is capable of producing new brain cells at any age, so use this book to keep your memory in top shape, boost brainpower, keep track of dates, schedules, tasks and phone numbers, and become more productive today!